Przemoc hermeneutyczna. O analogicznej rekonstrukcji obecności - Gan-Krzywoszyńska, Katarzyna; Leśniewski, Piotr (Wydawnictwo Naukowe Instytutu Filozofii UAM, 2016)
The aim of the paper is to analyze the relation between hermeneutic violence and univocal semantics. Furthermore, we argue that hermeneutic violence although it concerns post mortal time span is as much dangerous as physical and psychological violence, since hermeneutic violence affects even whole generations of victims. The article contains also a brief presentation of analogical perspective in contemporary philosophical conceptions by Enrique Dussel and Mauricio Beuchot. Following Reyes Mate we claim that memory is of fundamental importance of any adequate and effective theory and especially practice of justice.
Keywords: violence; hermeneutic death; analogy; memory